Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1093/cid/cis1210
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma genitalium Incidence, Organism Load, and Treatment Failure in a Cohort of Young Australian Women

Abstract: Although MG incidence was relatively low, testing should be recommended for women considered to be at increased risk based on sexual history. Our results also suggest that organism load might be important in azithromycin treatment failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 29 publications
1
50
0
1
Order By: Relevance
“…Several recent studies have highlighted that azithromycin (AZM)-resistant M. genitalium strains are emerging worldwide (35)(36)(37)(38)(39)(40)(41)(42), two of which provide molecular evidence that resistance can be induced with 1 g of STAT dosing (38,42). Using conventional PCR and Sanger sequencing, analysis of the M. genitalium-positive subjects in this study showed that none of their infecting strains possessed mutations that confer macrolide resistance (data not shown).…”
Section: Resultsmentioning
confidence: 71%
“…Several recent studies have highlighted that azithromycin (AZM)-resistant M. genitalium strains are emerging worldwide (35)(36)(37)(38)(39)(40)(41)(42), two of which provide molecular evidence that resistance can be induced with 1 g of STAT dosing (38,42). Using conventional PCR and Sanger sequencing, analysis of the M. genitalium-positive subjects in this study showed that none of their infecting strains possessed mutations that confer macrolide resistance (data not shown).…”
Section: Resultsmentioning
confidence: 71%
“…Of those with pretreatment macrolide resistance mutations 1 of 1 failed the 5-day regimen15 and 49 of 56,23 0 of 2,26 12 of 16,21 6 of 6,19 0 of 125 and 8 of 1017 failed azithromycin 1 g. Thus, 76 of 92 (82.6%, 95% CI 73.3% to 89.7%) individuals with a macrolide resistance mutation failed treatment with azithromycin.…”
Section: Resultsmentioning
confidence: 98%
“…One was a study of a random sample of men with NGU treated with azithromycin 1 g who were identified as MG positive 24 25. One was a female only study designed to test incidence, organism load  and treatment failure after treatment with azithromycin 1 g 26. One was a prospective longitudinal cohort study comprising an observational study and a randomised treatment trial involving both men and women 17.…”
Section: Resultsmentioning
confidence: 99%
“…In M. pneumoniae, a close relative of M. genitalium, most resistant strains harbor the A2058 mutation (26). Macrolide resistance in M. genitalium is associated with therapeutic failure of 1 g azithromycin in about 85% of patients infected by a mutant strain (4), and selection of macrolide-resistant mutants during azithromycin treatment has been reported by several studies (9,12,15,27). In our study, we also observed the selection of macrolide resistance for 2 patients, patient 2 in 2011 and patient 17 in 2012.…”
Section: Discussionmentioning
confidence: 99%